Is rated debt arm's length? Evidence from mergers and acquisitions - Reint E. Gropp; Christian Hirsch; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
In this paper we challenge the view that corporate bonds are always arm's length debt. We analyze the effect of bond ratings on the stock price return to acquirers in M&A transactions, which tend to have significant effects on creditor wealth. We find acquirers abnormal returns to be higher if they are unrated, controlling for a wide variety of other effects identified in the literature. Tracing the difference in returns to distinct managerial decisions, we find that, everything else constant, rated firms increase their leverage in takeover transactions by less than their unrated counterparts. Consistent with a significant role for rating agencies, we find monitoring effects to be strongest when acquirer bonds are rated at the borderline between investment grade and junk. Finally, we are able to empirically exclude a large number of alternative explanations for the empirical regularities that we uncover.
urn:nbn:de:hebis:30-101925
Keywords: G21; G24; G32; G34; 330; Acquisitions; Credit Ratings; Mergers and Acquisitions; Arm's Length Debt; Abnormal Returns; Übernahme; Industrieobligation; Kreditwürdigkeit; Kapitalstruktur; Kapitalertrag; Schätzung; USA